The nature of science in Islam (philosophical analysis) - Guswenti, Mirna; Nadia, Kholimatus (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
Science is something of great urgency in learning by having the primacy of the subject of thinking, in which the process of fostering a mindset and maturity of action can be realized in problem-solving and socializing. From a philosophical point of view, science is actually formed because humans try to think further about the knowledge they have. The purpose of writing this scientific paper is to find out, identify, and understand science in Islam in the form of (1) its essence (2) objectives (3) implementation in Islam. The type of writing is library research, namely obtaining reference sources from books related to the discussion, the holy book of the Qur'an, and journals are indicated by ISSN. The writing in this scientific work can be divided into two data methods which are interconnected, namely: primary data used as the main object is the book on Islamic education philosophy by Ramayulis, Margustam, and Hasan Basri. Meanwhile, secondary data sources are used by the author as a treasure trove of thinking that has relevance to science in the discussion of this writing. After obtaining the appropriate data, then it is analysed by using inductive techniques.